Penerapan Model Pembelajaran Missouri Mathematics Project (MMP) terhadap Peningkatan Kemampuan Penalaran Matematis Siswa - Nia Kurniawati; Uba Umbara; Evan Farhan Wahyu Puadi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
This research presents the findings of a study on the use of learning mathematics by using model Missouri Mathematics Project to increase students' mathematical reasoning abilities. The study involved an experimental class and control class is taken from the eighth grade at SMP Negeri 1 Cimahi in the second semester of the academic year 2015-2016. Research using essay test instruments to evaluate students' mathematical reasoning abilitiy and use students' responses to determine the students' response to learning that is used. To compare the ability of the two classes, the researchers used one-way t test for two independent samples. While to analyze the hypothesis concerning the gain classroom experiments, the researchers used one sample t test. From the results of the pretest known that the mean score of control class of mathematical reasoning is 13,25 while the experimental class is 12,30. Through t test on the value of the note that the value tcount = -0,51. While the degree of freedom df = 5% and 56 known ttable = 2,0042 From both these data we know that - 2,0042